Application of Trichoderma harzianum in Breaking Dormancy and Growing Porang (Amorphophallus muelleri Blume.) Bulbil Buds - Trovicana, Kinrara Yuri; Yuliani, Yuliani (LenteraBio : Berkala Ilmiah Biologi, 2026)
Propagation of porang through bulbil is considered effective, but it has the drawback of relatively long dormancy period. Trichoderma harzianum can stimulate IAA production through the tryptophan biosynthesis pathway. This study aims to describe the effect of Trichoderma harzianum in breaking dormancy and promoting the growth of porang bulbil shoots. The method used was a factorial Randomized Block Design with three repetitions. The first factor was the concentration of Trichoderma harzianum (0%, 25%, 50%, and 100%), accompanied by an auxin control. The second factor was soaking duration (1 hour, 3 hours, and 6 hours). Parameters for breaking dormancy included the vigor index and sprouting time. The parameters for bud growth consisted of the number of buds, the length of the buds, and the length of the root buds. The results show that the concentration of Trichoderma harzianum and the duration of soaking significantly affect all parameters. The interaction between the two factors did not substantially affect the vigor index, sprouting time, and number of sprouts. However, it significantly affected the length and root length of the sprouts. The combination of 100% Trichoderma harzianum and 6 hour soaking duration was the optimal treatment for all parameters.